Restor Environmental Awareness of Sufism Perspectives Due to the Lack of Human Spirituality Values - Reni Dian Anggraini (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The environmental phenomenon that occurs is the result of the lack of spiritual values in humans, giving rise to a crisis in the environment. Humans are only concerned with their ego and also concerned with their ego in order to achieve what they want. Therefore, the purpose of this paper is to try to restore awareness of the environment by means of Sufism so that it can restore the value of spirituality in humans. So the author uses a research method in the form of library research or library research, by collecting various related sources. Whether it's from books, journals and other articles related to the theme that the author adopts. The author collects data obtained from various related sources so that they make it into an article. The results of this paper indicate that the environmental crisis that occurs is caused by the actions of modern humans today who greatly glorify science and technology. So that modern humans are only fixated on their rational attitudes without thinking about the effects that will occur in the future. Therefore, a noise arises in himself so that humans feel the emptiness within themselves. Therefore, to restore awareness of the environment and also spirituality in humans, you can use Sufism. Sufism can be the basis of ethics to restore awareness of the environment through the process of zuhud, wara 'and faqir